Adherence to follow‐up after the exit cervical cancer screening test at age 60–64: A nationwide register‐based study. (12th November 2021) - Jørgensen, Susanne F.; Andersen, Berit; Petersen, Lone Kjeld; Rebolj, Matejka; Njor, Sisse H.
Abstract: Background: In Denmark, human papillomavirus (HPV) testing has replaced cytology in primary cervical cancer screening for women aged 60–64; at this age, women are invited for the last (exit) screening test within the national organized program. Aim: We investigated the adherence of these women to the recommended follow‐up after a non‐negative (positive or inadequate) HPV test and the overall resource use during that follow‐up. Materials & Methods: We included all 2926 women aged 60–64 years with nonnegative HPV screening tests between March 2012 and December 2016. All relevant follow‐up tests and procedures were retrieved until the end of 2020 from the highly complete Danish administrative health registers, and the data were linked at the individual level. We determined the extent to which the adherence patterns followed the national recommendations for follow‐up and estimated the total numbers of tests and diagnostic procedures utilized during the entire process. Results: In total, only 26% of women had follow‐up in accordance with the recommendations; 4% had no follow‐up, 46% had insufficient follow‐up, and 24% had more follow‐up than recommended. We estimated that 17% of women remained in follow‐up for longer than 4 years. The average numbers of diagnostic tests and procedures used after positive HPV screening were higher than expected, even among women who had insufficient follow‐up, that is, those who received less invasive procedures than recommended, or experienced delays in receiving those procedures. Conclusion: To conclude, we found that the patterns of follow‐up of women with nonnegative primary HPV screening tests at 60–64 often diverged from the recommendations. Addressing these inconsistencies in follow‐up by providing evidence for optimal clinical management should help improve the quality of screening programs and secure an equal and reliable follow‐up care service for all women. Abstract : We mapped the entire follow‐up pathways after positive HPV exit screening among women aged 60–64 years. Only one fourth of the women complied to the national recommendations for follow‐up and we found extensively long and apparently individualized pathways. There is an urgent need for evidence‐based guidelines with clear recommendations for when to end screening and the associated follow‐up in this age group.